Algorithms and Ordering Heuristics for Distributed Constraint Satisfaction Problems - Wahbi (Wiley Data and Cybersecurity, 2013)
Monograph
fulltext
Keywords: Computing and Processing; Communication, Networking and Broadcast Technologies